Propofol inhibits pancreatic cancer progress under hypoxia via ADAM8. (11th May 2019) - Gao, Yutong; Yu, Xiangdi; Zhang, Fangxiang; Dai, Jing
Abstract: Background: To investigate the potential anti‐tumoral properties of propofol in pancreatic cancer and elucidate the underlying mechanisms. Methods: The relative expression of ADAM metallopeptidase domain 8 (ADAM8) in response to hypoxia in Panc1 cells was analyzed by western blotting. The enzymatic activity was determined by fluorescence release from PEPDAB013 decomposition. Cell growth was measured via cell counting and cell viability was measured using CCK‐8 kit. Cell migrative capacity was evaluated by transwell and adhesion assay. The relative abundance of angiogenesis‐related markers including platelet‐derived growth factor AA, angiogenin, endothelin‐1 and vascular endothelial growth factor were determined by real‐time polymerase chain reaction and western blotting. The anti‐tumoral activity of propofol was investigated with Panc1‐derived xenograft mice model. Results: ADAM8 was significantly induced by hypoxia and efficiently inhibited by co‐treatment with propofol. Propofol suppressed proliferation and compromised viability of Panc1 cells. In addition, the migrative capacity was greatly inhibited by propofol dosage. Comprehensive profiling of angiogenesis‐related markers demonstrated that propofol remarkably suppressed neovascularization response in Panc1 cells under hypoxia. We further uncovered that propofol administration via subcutaneous injection delayed xenograft tumor progression. Conclusion: Propofol specifically inhibited ADAM8 expression and activation in response to hypoxia in pancreatic cancer, and held great value for therapeutic effects. Abstract : Highlight Setting out to investigate the anti‐tumoral properties of propofol and elucidate the underlying mechanisms, Gao and colleagues concluded that propofol specifically inhibits ADAM8 expression and activation in response to hypoxia in pancreatic cancer, and suppresses cell proliferation and migrative capacity in Panc1 cells, underlining its potential for clinical application.